PEMANFAATAN POHON SAGU (Metroxylon sp) DAN KUALITAS PATI SAGU DARI DESA SALIMURAN KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Ayu Aulia Kurnia Putri; Fatriani Fatriani; Trisnu Satriadi (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to identify the utilization of sago tree, production of sago starch, and analyze its quality.  Sampling was carried out in Salimuran Village, Kusan Hilir District, Tanah Bumbu Regency.   The data of utilization and production of sago are collected by interview and discussion with Sago workers.  The quality of sago starch is measured based on SNI 3451-2001 and SNI 3751-2009for carbohydrates, proteins and water content, and SII No. 0418-81-2001 for sugar content. The part of the plant that is used by the Salimuran village community is sago starch for food, leaves for roofing materials and bark for fuel wood. Sago with a length of 6 m and a diameter of 50-60 cm can produce as much as 6-7 sacks of starch or equivalent to 89 - 91 kg. Sago starch from Salimuran village contains carbohydrates of 48.92%, sugar content of 54.34%, protein 0.67% and water content of 4.10%. This data shows that only the water content is in accordance with the standard (SNI).Keywords: Sago; utilization; production; quality; and Salimuran Village